Finger Millet: A Potential Commodity for Nutritional Security and Entrepreneurship Development – A Perspective - Patel, S; Pisalkar, P S (Journal of Postharvest Technology, 2015)
Finger millet (Eleusine coracana L.), one of the small millets, is known for several health benefits and some of the health benefits are attributed to its polyphenol and dietary fiber contents. It is an important staple food in India for people of low income groups. Finger millet is comparable to rice with regard to protein (6-8%) and fat (1-2%) and is superior to rice and wheat with respect to mineral and micro-nutrients. It is a major source of dietary carbohydrates for a large section of the society specially the people residing in the tribal and forest belts. Nutritionally, its importance is well recognised because of its high content of calcium (344 mg/100 g), dietary fiber (22 g/100 g) and phenolic compounds (0.3 – 3%). Finger millet is also recognised for its health beneficial effects, such as anti-diabetic, antioxidant and antimicrobial properties. However, its utilization in the daily dietary at present is confined to the areas where it is grown only. Unavailability of products to the taste of urban mass is the main reason capping the utilization. Processing the finger millet using traditional as well as modern techniques for the development of value added products would be the possible solution to enhance the consumption of this important commodity.